2016
DOI: 10.1159/000441348
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Fixed-Dose Perindopril Arginine/Amlodipine in Hypertensive Patients Not Adequately Controlled with Amlodipine 5 mg or Perindopril <b><i>tert</i></b>-Butylamine 4 mg Monotherapy

Abstract: Objectives: To assess the blood pressure-lowering efficacy and tolerability of perindopril/amlodipine fixed-dose combinations in Chinese patients with mild-to-moderate essential hypertension not adequately controlled with monotherapy alone. Methods: In 2 separate double-blind studies, patients received a 4-week run-in monotherapy of amlodipine 5 mg or perindopril 4 mg, respectively. Those whose blood pressure was uncontrolled were then randomized to receive the fixed-dose combination of perindopril 5 mg/amlodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…After 8 weeks, the mean SBP in the perindopril/amlodipine FDC (5/5 mg) showed a mean reduction of 11.1 ± 11.9 mmHg compared to a mean reduction of 8.5 ± 11.1 mmHg SBP in the amlodipine 5-mg group ( p = 0.0095). Mean SBP decreased to 15.8 ± 12.1 mmHg in the perindopril/amlodipine FDC group compared with 7.8 ± 13.7 mmHg in the perindopril 4-mg group ( p < 0.0001) ( Hu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After 8 weeks, the mean SBP in the perindopril/amlodipine FDC (5/5 mg) showed a mean reduction of 11.1 ± 11.9 mmHg compared to a mean reduction of 8.5 ± 11.1 mmHg SBP in the amlodipine 5-mg group ( p = 0.0095). Mean SBP decreased to 15.8 ± 12.1 mmHg in the perindopril/amlodipine FDC group compared with 7.8 ± 13.7 mmHg in the perindopril 4-mg group ( p < 0.0001) ( Hu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were 14 studies that reported the safety of perindopril/amlodipine FDC ( Supplementary Table S2 ). Of these, several serious but rare emergent adverse events (EAEs) of perindopril/amlodipine FDC have been reported, including stroke, brain infarction, cataracts, and diaphragmatic eventration ( Hu et al, 2016 ). In the study by Fleig et al, eight patients (0.4%) experienced severe EAEs in 140 ADR of 88 patients, of which four patients (0.2%) did not recover and one patient died with a hypertensive crisis ( Fleig et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven SPC were compared, namely Amlodipine/valsartan (8 studies), 12,[21][22][23][24][25][26][27] Telmisartan/amlodipine (5 studies), 13,[28][29][30][31] Losartan/HCTZ (4 studies), [32][33][34][35] Candesartan/HCTZ (4 studies), 32,[36][37][38] Amlodipine/benazepril (3 studies), [39][40][41] Telmisartan/HCTZ (3 studies), 13,23,30 Valsartan/HCTZ (3 studies), 12,42,43 Irbesartan/amlodipine (2 studies), 44,45 Amlodipine/losartan (2 studies), 35,46 Irbesartan/HCTZ (1 studies), 47 Perindopril/amlodipine (1 studies). 48 The outcomes included were mainly systolic blood pressure, diastolic blood pressure, blood pressure control rate, and diastolic response rate after treatment. The characteristics of the included studies are shown in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%